2015
DOI: 10.1097/qco.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

The role of surveillance systems in confronting the global crisis of antibiotic-resistant bacteria

Abstract: Purpose of Review It is widely accepted that infection control, advanced diagnostics, and novel therapeutics are crucial to mitigate the impact of antibiotic-resistant bacteria. The role of global, national and regional surveillance systems as part of the response to the challenge posed by antibiotic resistance is not sufficiently highlighted. We provide an overview of contemporary surveillance programs, with emphasis on Gram-negative bacteria. Recent Findings The World Health Organization and public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 36 publications
1
37
0
5
Order By: Relevance
“…An earlier study in Uganda also found that of the patients who sought treatment at private clinics within 1 week of onset of symptoms, only 7% of them were properly managed. [16][17][18][19][20][21][22] Similar findings have been documented in Ghana where a high proportion, 70% of the respondents, practiced self-medication, and the most common antibiotic used was amoxicillin. 23 It is noted that the majority of drug shops (53.3%), were injecting patients probably with gentamicin and penicillin, to treat other bacterial infections like skin infections and urethritis or urinary tract infections.…”
Section: Discussionsupporting
confidence: 75%
“…An earlier study in Uganda also found that of the patients who sought treatment at private clinics within 1 week of onset of symptoms, only 7% of them were properly managed. [16][17][18][19][20][21][22] Similar findings have been documented in Ghana where a high proportion, 70% of the respondents, practiced self-medication, and the most common antibiotic used was amoxicillin. 23 It is noted that the majority of drug shops (53.3%), were injecting patients probably with gentamicin and penicillin, to treat other bacterial infections like skin infections and urethritis or urinary tract infections.…”
Section: Discussionsupporting
confidence: 75%
“…Active surveillance and antimicrobial stewardship efforts are essential to combat this threat to patient safety across all health care settings (23, 24). In the present survey, we examined the in vitro susceptibility profiles of 6,485 isolates of GPC and GNB from European and U.S. medical centers for the year 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Active surveillance and antimicrobial stewardship efforts are essential for combating this threat to patient safety across all health care settings (3,19). In the present survey, we have established the baseline in vitro susceptibility profiles of omadacycline for 69,246 isolates of GPC and GNB from medical centers in the APAC region, EU, LA, and NA for the years 2010 and 2011.…”
mentioning
confidence: 99%
“…In the United Kingdom, it is estimated that drug-resistant infections might account for 10 million deaths per year by 2050, with total costs of $100 trillion in lost output (1). Collection of AMR surveillance and antibiotic consumption data is an essential approach to both defining the scope of the resistance problem and developing interventions that improve appropriate use of antibiotics and decrease resistance selection pressure (1,3). Another important effort is to understand the mechanisms of resistance whereby bacteria avoid the effects of antibiotics and to use this information to develop new agents, or modify older agents, such that potent activity is retained against the key target pathogens (4-6).…”
mentioning
confidence: 99%